Information quality requirements for a nutrition app based on experts interviews - Mohammed, Siti Asma; Ighe, Mohamed Aden; Nordin, Azlin (Springer Science and Business Media Deutschland GmbH, 2022)
Book cover International Conference of Reliable Information and Communication Technology